Sleep duration and the risk of metabolic syndrome – a cross-sectional study - Suliga, Edyta; Kozieł, Dorota; Cieśla, Elżbieta; Rębak, Dorota; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2017)
Introduction: It has been stated that besides the traditional elements of lifestyle such as diet and physical activity, an additional factor, namely sleep, is involved in metabolic processes, hormonal functions, and energy homeostasis. Aim of the research: To examine relationships between self-reported sleep duration and the risk of metabolic syndrome (MetS) and its components, both for men and women. Material and methods: The study involved 10,367 individuals, aged 37 to 66 years. The definition of MetS applied in this paper was developed by the International Diabetes Federation (IDF). Logistic regression was applied to assess the risk (odds ratio – OR) of MetS and its components. Results : There was no relationship observed between short sleep duration (≤ 6 h) and the risk of MetS. Long sleep duration (≥ 9 h) was connected with a higher risk of MetS only in the unadjusted model (OR = 1.11). After adjusting for confounders, a significant association was found between long sleep duration and a higher risk of abdominal obesity in the test group as a whole (OR = 1.16), as well as in the men in the group (OR = 1.22). In women, both with short (OR = 1.08) and long (OR = 1.12) sleep duration, the risk of increased concentration of glucose was found. Conclusions : Our study did not confirm the existence of an association between inadequate sleep duration and the risk of MetS, defined in accordance with IDF criteria. Sleep duration, however, is connected with some of the MetS components. It is therefore necessary to conduct further, long-term tests in this regard.